Analisis Iuran dan Kamar Rawat Inap Standar di Badan Penyelenggara Jaminan Sosial Kesehatan dalam Perspektif Maqashid Syariah - Zamzam Mubarok; Amrizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research began with the issue of national health insurance contributions which basically became a polemic in society regarding obtaining health insurance by the Government in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia. Health is an important aspect in fulfilling human rights and is a benchmark. welfare in society.The aim of this research is to analyze the implementation of contributionsSocial Security AdministratorHealth from the Maqashid Sharia Perspective. To analyze Maqasid Syariah's views on the increase in contributions for health insurance. To analyze Moaqasid Syariah's views on the implementation of standard inpatient rooms. Object of researchSocial Security AdministratorHealth, this type of research is normative qualitative, the data source used is secondary data in the form of regulations relating to BPJS Health, fatwas from the ulama council. The data analysis technique used in this research was descriptive analysis.First research results: Implementation of contributions from the Social Security Administering Agency Health from the Maqasid Syariah perspective is an important effort in realizing a just, equitable and sustainable health system. By continuing to improve efficiency, transparency and service quality, this system can be more effective in achieving the main objectives of Sharia, namely protecting and promoting the welfare of individuals and society as a whole. Second, from the Maqasid Syariah point of view, the increase in contributions in health insurance is acceptable and is even necessary if (1) It is carried out with the principles of justice and solidarity. (2) Increases access and quality of services. (3) Transparency and accountability, (4). Not burdening the underprivileged. Third, from the perspective of Maqasid Syariah, the implementation of inpatient class standards in the Social Security Administering Body supports the main objectives of Sharia in the following way: (1). Increasing Justice and Solidarity, (2). Guaranteeing Mental Health and Safety, (3) Improving Mental and Intellectual Well-being (4). Protecting the Health of Future Generations, (5). Managing Resources Efficiently.